Digitalization of Licensing Services Through OSS-RBA as a Modern Governance Innovation in Lubuk Linggau City - Hendra Gunawan; Alfitri Alfitri; Andries Lionardo; M. Husni Thamrin; Ryan Adam (Green Publisher Indonesia, 2025)
The licensing process at the regional level is often convoluted, slow, and prone to information asymmetry. The digitalization initiative through the Online Single Submission Risk-Based Approach (OSS-RBA) in Lubuk Linggau City aims to simplify procedures and increase transparency. This study explores applicants’ and officials’ experiences with OSS-RBA, identifying factors that facilitate or hinder its implementation in local business licensing. Using a descriptive qualitative approach, data were gathered through semi-structured interviews with business actors of various scales and government officers, observations of service flows both at counters and online, and reviews of SOPs and related documents. Findings are presented narratively, highlighting categories and illustrative quotes. Respondents noted a clearer process flow, greater certainty about requirements, and easier tracking of application status through system notifications. Positive experiences were most common with low-risk licenses and among applicants familiar with OSS-RBA. New users expressed a need for initial guidance, detailed instructions, and accessible consultation channels. Key obstacles included digital literacy, network stability, inter-system connectivity, adaptation to new workflows, and SOP updates within local agencies. Stakeholders perceive OSS-RBA in Lubuk Linggau City as a more accessible, transparent, and consistent service. The results emphasize the need to improve communication about requirements, provide early support for new applicants, and enhance system integration to deliver a uniform user experience and sustain the benefits of digitalization.